(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, we will talk about modeling in linguistics, in particular about the applicative model, its specific features. The study also analyzed the relationship and various aspects of the applicative model with the processes of transformation and derivation. At the same time, the article considers the formation of derived words by the applicative method, operand, operator and applicator terms in lexical derivation on the basis of examples.